Measuring the application of total quality management in Karkh Maternity Hospital from the perspective of health staff - عطشان, فوزي هاشم; كاظم, ايمان عبد الغني (Journal of Economics and Administrative Sciences, 2019)
Quality is the key to success in today's world, which is based mainly on competition in the provision of high quality services through the application of the modern management method which is called  total  quality management in organizations. This includes describing the provision of health services and satisfaction of patients .              .                                                            Aim :  the aim of this study was to Measuring the application of total quality management  in Karkh maternity  Hospital  from the opinions of paramedical  staff to the importance of the total quality management in Alkarkh  maternity  hospital in the Baghdad Karkh health directorate  because its specialized hospital for maternity and  get the title  or (nickname) of the hospital friend of the child  .                                                                                                                  Methodology :  based on the descriptive and analytical methods , in order to test the hypothesis of this study we used  test of  stability (Cronbach Alpha) and  test of  (Kolmogorov-Smirnov) , frequencies and percentages through the statistical package program of social sciences SPSS V.16  to analyze the data which collected by relying on a questionnaire  which  is distributed to paramedical staff at Karkh  maternity Hospital , The sample size included all paramedical staff  in the hospital included were (100) individuals the  percentage of response was (91%)  ,during the period  May ,June and July  2018                                               Results:                                                                                                                  - The search  showed that the health staff in Karkh  maternity  hospital are perceive and understood   the concept  of importance of the of total quality management , with  high degree  of perception to all  three parts  (principles, advantages and obstacles) for total  quality management    - The sequence of the three axis principles according to the level of perception of the research sample from the top to the lowest (the  axis principles first and then the axis of the advantage and finally the axis of obstacles to the application of total quality management- The search showed a relationship between the demographic variables of the study sample (age, gender, job title and years of experience) and the perception of the health staff at Karkh  maternity hospital for the  concept of the importance of  application of total quality management